Challenges in the regulation of occupational risk management in Brazil - Gonçalves Filho, Anastácio Pinto; Leal, Diego Pinto de Barros (Revista Principia, 2025)
Occupational accidents and illnesses pose a serious public health issue in Brazil. Recognizing this, Brazilian government authorities have acknowledged the need to implement measures to improve environmental work conditions, and equipment control, and promote occupational safety and health. The complexity of workplace health and safety in Brazil is partly due to the country's diverse range of companies, which vary in technological levels, sizes, motivations, resources, and competencies, with the majority being micro and small enterprises (MSEs). This study aims to investigate whether the strategy adopted by Brazil since 2022 to regulate occupational risk management and promote occupational health and safety has been complied with by companies. To achieve this, all notices of violation related to occupational risk management were analyzed from January 2022 to June 2023. In total, 5,547 cases of violations were examined. In total, 5,547 cases of violations were examined. It was concluded that the occupational risk management regulation strategy alone is insufficient, as many companies have not implemented these measures. There is a need to improve labor inspection services. Safety and health regulatory bodies should be strengthened to consistently and thoroughly conduct workplace inspections and ensure compliance with regulations. Additionally, increasing fines for non-compliance with occupational safety and health regulations is imperative. Public policies and interventions encouraging MSEs to adhere to occupational risk management and invest in workplace improvements are essential.